Information Resources of the Ukrainian Science in the History of the National Revival as a Factor of Consolidation of the Educational space of Ukrainein the First Third of the 20 th Century - Petrykova, Valentyna (Київський національний університет імені Тараса Шевченка, 2018)
A new methodological approach within the modern theory of information society considers the history of the formation of the Ukraine scientific space in the first third of the twentieth century. The attention is focused on the factors of European identity in evaluation historical facts of establishment and development of national complex bibliological science and practice. The bibliological practice history of Ukrainian scientists is examined as a means of scientific forces consolidation in the system of Ukrainian knowledge. Organizational work on the consolidation of forces conducted research on regional and edge scientific societies. Determining the strategic objectives of science based on mandatory summarizing scientific heritage by means of historiography, bibliological, bibliography, book science. Bibliological considered the achievements of scientists the Scientific society named after Shevchenko, the Ukrainian scientific society, University schools of Kiev, Kharkov and Odessa. The value characteristics of author's scientific bibliography of works contributed to the formation of the consolidated information resources of science of Ukraine. The issues of establishing a system of information equipment, the national science studied through the functionality of bibliographic commissions in the structure of Scientific society of the name Shevchenko, the Ukrainian scientific society, Ukrainian Academy of Sciences. In the base activity factor of the Ukrainian intelligentsia in the direction of resource the sum of knowledge in the first third of the twentieth century objective recognized the consequences of the nineteenth century end information revolution.Keywords: bibliology, bibliographic сommission, informative revolution, informative resources, informative society, scientific societies, Ukrainian academy of sciences.

Валентина ПетриковаЗапропоновано новий методологічний підхід до розгляду історії формування наукового простору України в першій третині ХХ століття в межах сучасної теорії інформаційного суспільства. Акцентовано увагу на чинниках європейськості при оцінюванні історичних фактів становлення та розвитку національного комплексу бібліологічної науки і практики. Історія бібліологічної  практики українських  вчених розглядається  як засіб консолідації наукових сил в системі українознавчого знання. Організаційно робота по консолідації наукових сил проводилась по регіональних та крайових наукових товариствах. Визначення стратегічних завдань науки грунтувалось на обов’язковому підсумуванні наукового доробку засобами історіографії, бібліології, бібліографії, книгознавства. Розглянуто бібліологічний доробок вчених НТШ, УНТ, університетських наукових шкіл Києва, Харкова, Одеси. Ціннісні ознаки авторських науково-бібліографічних праць сприяли формуванню консолідованих інформаційних ресурсів науки України. Питання налагодження системного інформаційного забезпечення національної науки досліджено через функціональні можливості бібліографічних комісій в структурі НТШ, УНТ, УАН. За базовий чинник активності дій української інтелігенції в першій третині ХХ ст в напрямі ресурсного підсумування знання. визнано об’єктивні наслідки другої інформаційної революції кінця ХІХ ст.Ключові слова: бібліологія, бібліографічна комісія, інформаційна революція,інформаційні ресурси, інформаційне суспільство, наукові товариства, Українська академія наук.
Інформаційні ресурси української науки в історії національного відродження як фактор консолідації наукового простору України в першій третині ХХ століття